Prolanis Implementation Effective to Control Fasting Blood Sugar, HBA1C and Total Cholesterol Levels in Patients with Type 2 Diabetes - Musfirah Ahmad; Rini Rachmawaty; Elly L. Sjattar; Saldy Yusuf (Jurnal Ners, 2017)
Introduction: Diabetes mellitus (DM) is a global disease endemic and causing of 4.6 million deaths in the world. The Indonesian government and health insurance [BPJS Kesehatan] formulate a Chronic Disease Care Program [Program Pengelolaan Penyakit Kronis (PROLANIS)] for type 2 diabetes that aimed at controlling the glycemic status and the risk factors of macro and microvascular complications. The purpose of this study was to analyze the correlation between the implementation of PROLANIS and fasting blood sugar, HbA1c, and total cholesterol levels in patients diagnosed with type 2 diabetes at Antang and Pampang community health centers, Makassar, Indonesia.Methods: This study used descriptive correlation design with cross sectional study approach. Subjects were 40 patients diagnosed with type 2 diabetes who joined PROLANIS at PUSKESMAS Antang and Pampang, Makassar, with sampling technique used was total sampling. The data were analyzed using correlation test to assess the significance (p), the direction (+/-), and the strength of the correlation (r). The implementation of PROLANIS was measured by using the observation sheets developed based on BPJS Kesehatan criteria, while the fasting blood sugar, HbA1c, and total cholesterol levels were checked by laboratory.Results: The mean of the implementation of PROLANIS was 15.05 (SD ± 5.62), while the mean levels of fasting blood sugar, HbA1c, and total cholesterolwere as followed: 191.80 mg/dL (SD ± 85.15); 8.4% (SD ± 2.08); and 192.87 mg/dL (SD ± 45.07). Using the Spearman's rho test, the study result showed that there was a significant and negative correlation between the implementation of PROLANIS and the levels of fasting blood sugar (p= 0.001; r= -0.724), HbA1c (p= 0.001; r= -0.870), and total cholesterol (p= 0.029; r= -0.35) in patients diagnosed with type 2 diabetes at Puskemas Antang and Pampang, Makassar.Conclusion: The optimal implementation of the PROLANIS is very effective to control the levels of fasting blood sugar, HbA1c, and total cholesterol in patients type 2 diabetes.